Human Capital and Economic Growth: Empirical Evidence for South America - Cerquera Losada, Oscar Hernán; Clavijo Tovar, María de los Ángeles; Pérez Peña , Carla Yanella (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper evaluates the relationship between education and economic growth in 8 South American countries for the period 2003-2018. A model of fixed effects panel data was estimated. As a measure of human capital two indicators were used, the United Nations Development Programme (UNDP) Education Index, and the Penn World Table 10.0 (PWT) human capital index; the purpose is to determine which of the two measures of human capital best explain the relationship between education and growth in South American economies. The results showed that exports per capita, education expenditure, fertility rate and gross capital formation are positively related to output per capita, and given the context of South American economies, the education index calculated by UNDP seems to be the most accurate indicator to measure the relationship between human capital and economic growth.